2005
DOI: 10.1007/s00424-005-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of skeletal muscle shortening velocity in mammals representing a 100,000-fold difference in body size

Abstract: To fully understand the effect of scaling on skeletal muscle shortening velocity (V (0)), it is important to know which phenotypic characteristics drive the changes between species. The purpose of the current investigation was to compare the effects of body mass and femur length, as an estimate of total limb length, on V (0) in species that cover a 100,000-fold range of body masses. Using the slack test procedure, V (0) was determined for fibers expressing types I and IIa myosin heavy chain (MyHC) isoforms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 54 publications
3
46
2
Order By: Relevance
“…The between-species changes in mechanical properties with body size observed in the current study are different to what might be expected from previous literature comparing scaling relationships across species from widely different groups of animals (Seow and Ford, 1991;Rome et al, 1990;Medler, 2002;Pellegrino et al, 2003;Marx et al, 2006) or between individuals within a species. In general, the previous literature indicates that larger individuals have skeletal muscle mechanical properties indicative of slower fibre type.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The between-species changes in mechanical properties with body size observed in the current study are different to what might be expected from previous literature comparing scaling relationships across species from widely different groups of animals (Seow and Ford, 1991;Rome et al, 1990;Medler, 2002;Pellegrino et al, 2003;Marx et al, 2006) or between individuals within a species. In general, the previous literature indicates that larger individuals have skeletal muscle mechanical properties indicative of slower fibre type.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study found that the maximal shortening velocity of single muscle fibres decreased with increased body mass (M b ), from rat to rabbit to horse, scaling M b −0.18 in slow fibres and M b −0.07 in fast glycolytic fibres (Rome et al, 1990). Various scaling exponents have been found in other more recent studies comparing single fibres of the same fibre type between various mammalian species (Seow and Ford, 1991;Widrick et al, 1997;Pellegrino et al, 2003;Marx et al, 2006), with much of the variation in slope thought to be due to the species included in the study (Marx et al, 2006). A comprehensive review of published data demonstrated that maximal shortening velocity decreased with increased body mass, scaling across species M b −0.25 , whereas maximal isometric stress showed no significant relationship with body mass (Medler, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Differences in muscle size between large and small animals are mainly accounted by differences in the number and length of the fibers (Goldspink, 1977;Perry et al, 1988), whereas muscle fiber size has been shown to be independent from body size and rather depends on other physiological parameters, such as volume to surface ratio of the fibers (e.g., Burke, 1981;Armstrong and Phelps, 1984;Marx et al, 2006;Kinsey et al, 2007).…”
mentioning
confidence: 99%
“…This means, oxidative enzymes are less active and glycolytic enzymes are more active in smaller mammals. A smaller maximum velocity during unloaded shortening of muscle fibers expressing a given MHC was shown for larger mammals by Marx et al (2006). Furthermore, fast fibers of larger mammals showed a higher molecular weight of the myosin light chain isoform 1 (MLC1F) associated with structural changes leading to a higher affinity to the actin molecules, and thus, a lower ATPase activity and slower cross-bridge kinetics (Bicer and Reiser, 2007).…”
mentioning
confidence: 99%
“…slow, intermediate or fast) tends to correlate with animal size; the relative abundance of fast fibers decreases (i.e. showing a transition from MyHC IIB to MyHC IIX/A to MyHC I) as body mass increases (Pellegrino et al, 2003;Marx et al, 2006;Schiaffino and Reggiani, 2011). Another example in this area is work by Coughlin and colleagues (Coughlin et al, 2001;Campion et al, 2012) on several species of centrarchid fish.…”
Section: Body Weight Musculoskeletal Design and Locomotionmentioning
confidence: 99%